Fe-TAML encapsulated inside mesoporous silica nanoparticles as peroxidase mimic: femtomolar protein detection - Kumari, Sushma; Dhar, Basab B.; Panda, Chakadola; Meena, Abhishek; Sen Gupta, Sayam (ACS Applied Materials & Interfaces, 2014)
Peroxidase, such as horseradish peroxidase (HRP), conjugated to antibodies are routinely used for the detection of proteins via an ELISA type assay in which a critical step is the catalytic signal amplification by the enzyme to generate a detectable signal. Synthesis of functional mimics of peroxidase enzyme that display catalytic activity which far exceeds the native enzyme is extremely important for the precise and accurate determination of very low quantities of proteins (fM and lower) that is necessary for early clinical diagnosis. Despite great advancements, analyzing proteins of very low abundance colorimetrically, a method that is most sought after since it requires no equipment for the analysis, still faces great challenges. Most reported HRP mimics that show catalytic activity greater than native enzyme (similar to 40-fold) are based on metal/metal-oxide nanoparticles such as Fe3O4. In this paper, we describe a second generation hybrid material developed by us in which approximately 25 000 alkyne tagged biuret modified Fetetraamido macrocyclic ligand (Fe-TAML), a very powerful small molecule synthetic HRP mimic, was covalently attached inside a 40 nm mesoporous silica nanopartide (MSN). Biuret-modified Fe-TAMLs represent one of the best small molecule functional mimics of the enzyme HRP with reaction rates in water close to the native enzyme and operational stability (pH, ionic strength) far exceeding the natural enzyme. The catalytic activity of this hybrid material is around 1000-fold higher than that of natural HRP and 100-fold higher than that of most metal/metal oxide nanoparticle based HRP mimics reported to date. We also show that using antibody conjugates of this hybrid material it is possible to detect and, most importantly, quantify femtomolar quantities of proteins colorimetrically in an ELISA type assay. This represents at least 10-fold higher sensitivity than other colorimetric protein assays that have been reported using metal/metal oxide nanoparticles as HRP mimic. Using a human IgG expressing cell line, we were able to demonstrate that the protein of interest human IgG could be detected from a mixture of interfering proteins in our assay.
Keywords: colorimetrically; immuno assay; MSN; peroxidase mimic; signal amplification